FORECASTING CHARACTERISTICS OF COMPOSITE STRENGTH ON THE BASIS OF PREFORMS IN ELEMENTS OF BUILDING STRUCTURES: Array - Kondratiev, A.; Andrieiev, O. (Municipal economy of cities. Series: «Economy science», 2020)
Currently, wicker composite structures for various purposes are widely used in many industries. The use of such preforms allows to provide the possibility of automation of production, high speed and efficiency of the process of manufacturing polymeric composite materials and structures based on them. Knowledge of their properties allows you to optimize the production of structures with the necessary parameters during design. In the article the model of composite material on the basis of wicker reinforcement was further developed. For the practical implementation of this model, it is sufficient to test material samples with three different angles between the harnesses, for example, ± 30º, ± 45º and ± 60º. A mathematical description of the model is given. The model made it possible to predict the physical and mechanical characteristics of the composite material when it is laid out on curved surfaces. At the same time some fictitious limits of durability of a composite are defined. This is due to the fact that each value of the angle between the harnesses corresponds to its physical and mechanical characteristics of the unidirectional composite material. In this case, the ultimate strength curves necessarily pass through the points corresponding to the experimental data. The article shows that the possible deviations of the strength limits in the range of angles between the harnesses will lie within the range of characteristics obtained by testing. The article shows that in the realized interval of angles between the harnesses, almost any polynomial criterion of strength will accurately describe the strength of the composite reinforced with a braided sleeve. The obtained parameters, in contrast to the existing ones, allow to predict the strength characteristics of the composite on the basis of braided sleeves depending on the positioning and location of the material on the forming surface. The obtained results are the basis for solving the problems of calculating the strength of building structures from composite materials based on wicker preforms.